Reading Indonesian Criminal Code through the Lens of Surah Al-Maidah Verse 44 - Najib, M. Ainun; Candra, Marli; Khalil, Shahidra Abdul (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2024)
Abstract: Adherence to the teachings of Islamic law is obligatory for Muslims. The law is sacred and stems from revelation, whereas in a modern state system, the source of obligation comes from man-made law. This article will discuss Indonesian criminal law from the surah Al-Māidah verse 44 perspective and the potential seismic shift of Islamic criminal law becoming a positive law in Indonesia. This research is normative research, which examines law from written sources with a comparative approach. The results show that despite differences in several rules, Indonesian criminal law is in so far the philosophical perspective is in accordance with Islamic criminal law. The potential implications of this shift are significant, not only presenting a major change in the legal landscape of Indonesia but also opening up new avenues for legal research and discourse. Keywords: Islamic criminal law, Indonesian Criminal Code, Al-Māidah, Integration of Islamic law. Abstrak: Kepatuhan terhadap ajaran hukum Islam adalah kewajiban bagi umat Islam. Hukum itu suci dan berasal dari wahyu, sedangkan dalam sistem negara modern, sumber kewajiban berasal dari hukum buatan manusia. Artikel ini akan membahas hukum pidana Indonesia dari perspektif surah Al-Māidah ayat 44 dan potensi pergeseran seismik hukum pidana Islam menjadi hukum positif di Indonesia. Penelitian ini merupakan penelitian normatif, yang mengkaji hukum dari sumber tertulis dengan pendekatan komparatif. Hasil penelitian menunjukkan bahwa meskipun ada perbedaan dalam beberapa aturan, hukum pidana Indonesia sejauh ini dalam perspektif filosofis sesuai dengan hukum pidana Islam. Pergeseran potensial ini tidak hanya menghadirkan perubahan signifikan dalam lanskap hukum Indonesia, tetapi juga membuka jalan baru untuk penelitian dan wacana hukum. Kata kunci: Hukum Pidana Islam, KUHP Indonesia, Al-Māidah, Integrasi Hukum Islam.